PC Interfacing : Digital Filter Realization - Sadik, Amin Zeki (Sulaimani Journal for Pure and Applied Sciences, 2000)
As PCs architecture is continuing its migration to embedded systems , it has increasingly, been involved in real-time operation as controllers. The price-performance ratio of embedded versions of PCs is very attractive . The reducing learning time resulting from using a familiar architecture also tends to lower development cost . This opens the door for wide range of applications. An excellent signal processing application that can introduce this approach is the realization of digital filter. Digital filters have remarkable advantage over their analog counterparts; especially ,in low cut-off frequency responses . A very low cut-off-frequency digital filter has been designed and implemented by using the hardware resources of the PC . Various PC hardware facilities has been reviewed and efficiently used to carry out this research . The application program is developed and written using 'C' language .